2011
DOI: 10.1371/journal.pbio.1000599
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Desaturation Links Germ Cell Loss to Longevity Through NHR-80/HNF4 in C. elegans

Abstract: Lifespan extension induced by germline ablation in C. elegans is regulated by the nuclear hormone receptor NHR-80 in a process that requires the production of oleic acid by activation of the lipid desaturase FAT-6/SCD1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
286
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(299 citation statements)
references
References 33 publications
9
286
1
Order By: Relevance
“…In a previous study, Hugo Aguilaniu's laboratory reported that, in germline-less mutants too, NHR-80/HNF4 elevates the expression of enzymes responsible for converting a saturated fatty acid (SFA), stearic acid (SA, C16:0) into a mono-unsaturated fatty acid (MUFA), oleic acid (OA, C18:1n9). 21 We found that NHR-49/PPARa similarly controlled the expression of these desaturases in germline-less adults. Through lipidomic analyses, we further discovered that GSC-depleted adults showed an increase in unsaturated fatty acid (UFA) levels and a concomitant decrease in SFAs.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…In a previous study, Hugo Aguilaniu's laboratory reported that, in germline-less mutants too, NHR-80/HNF4 elevates the expression of enzymes responsible for converting a saturated fatty acid (SFA), stearic acid (SA, C16:0) into a mono-unsaturated fatty acid (MUFA), oleic acid (OA, C18:1n9). 21 We found that NHR-49/PPARa similarly controlled the expression of these desaturases in germline-less adults. Through lipidomic analyses, we further discovered that GSC-depleted adults showed an increase in unsaturated fatty acid (UFA) levels and a concomitant decrease in SFAs.…”
Section: Introductionmentioning
confidence: 66%
“…7,[15][16][17][18][19] Additionally, three members of the nuclear hormone receptor (NHR) family of transcription regulators, DAF-12/FXR, NHR-80/HNF4 and NHR-49/PPARa are important for GSC-less longevity. 7,[20][21][22] Multiple lines of evidence have indicated that these factors link lipid metabolism to reproductive stimuli and aging. DAF-16/FOXO3A, TCER-1/ TCERG1, SKN-1/NRF2 and DAF-12/FXR targets include lipid-metabolic genes, 15,19,20,[23][24][25] PHA-4/ FOXA-and HLH-30/TFEB-mediated enhancement of autophagy contributes to increased lipase activity 17,18 and NHR-80/HNF4 promotes fatty-acid desaturation in long-lived, GSC-less adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect occurred already after short-term exposure of the worms to 10 µM 17,18-EEQ, whereas long-term feeding and much higher concentrations were required to achieve similar effects with AA or EPA. Also other authors found that high concentrations and a minimal time of about 24 h are required to restore the phenotype of fat-3 mutants by C20-PUFA supplementation [43][44][45][46][47][48]. Remarkably, the exogenously administered 17,18-EEQ increased the locomotion activity already under normoxic conditions and was effective not only with the mutant but to a lesser extent also with wild-type worms.…”
Section: Discussionmentioning
confidence: 98%